3-D In Vitro Acoustic Super-Resolution andSuper-Resolved Velocity Mapping UsingMicrobubbles - Christensen-Jeffries,K; Brown,J; Aljabar,P; Tang,M; Dunsby,CW; Eckersley,RJ (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control, 2017)
Standard clinical ultrasound (US) imaging frequencies are unable to resolve microvascular structures due to the fundamental diffraction limit of US waves. Recent demonstrations of 2D super-resolution both in vitro and in vivo have demonstrated that fine vascular structures can be visualized using acoustic single bubble localization. Visualization of more complex and disordered 3D vasculature, such as that of a tumor, requires an acquisition strategy which can additionally localize bubbles in the elevational plane with high precision in order to generate super-resolution in all three dimensions. Furthermore, a particular challenge lies in the need to provide this level of visualization with minimal acquisition time. In this work, we develop a fast, coherent US imaging tool for microbubble localization in 3D using a pair of US transducers positioned at 90°. This allowed detection of point scatterer signals in 3 dimensions with average precisions equal to 1.9 µm in axial and elevational planes, and 11 µm in the lateral plane, compared to the diffraction limited point spread function full widths at half maximum of 488 µm, 1188 µm and 953 µm of the original imaging system with a single transducer. Visualization and velocity mapping of 3D in vitro structures was demonstrated far beyond the diffraction limit. The capability to measure the complete flow pattern of blood vessels associated with disease at depth would ultimately enable analysis of in vivo microvascular morphology, blood flow dynamics and occlusions resulting from disease states.